2022
DOI: 10.1111/eva.13446
|View full text |Cite
|
Sign up to set email alerts
|

A single genomic region involving a putative chromosome rearrangement in flat oyster (Ostrea edulis) is associated with differential host resilience to the parasite Bonamia ostreae

Abstract: European flat oyster (Ostrea edulis) is an ecologically and economically important marine bivalve, that has been severely affected by the intracellular parasite Bonamia ostreae. In this study, a flat oyster SNP array (~14,000 SNPs) was used to validate previously reported outlier loci for divergent selection associated with B. ostreae exposure in the Northeast Atlantic Area. A total of 134 wild and hatchery individuals from the North Sea, collected in naïve (NV) and long‐term affected (LTA) areas, were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
(139 reference statements)
2
10
0
Order By: Relevance
“…On the other hand, SNPs within DEGs showing genetic differentiation associated with the level of infection would be another relevant source of information for detecting consistent candidate genes holding allelic variants associated with resilience to the parasite. A similar approach has been recently reported in flat oyster O. edulis, where a major QTL related to resilience to Bonamia ostreae was identified (Vera et al, 2019;Sambade et al, 2022). Other selection models, such as overdominance, that have been reported for specific immune genes (Penn, 2002;Kekäläinen et al, 2009), could be operating and therefore our results would only explain part of the increased resilience.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…On the other hand, SNPs within DEGs showing genetic differentiation associated with the level of infection would be another relevant source of information for detecting consistent candidate genes holding allelic variants associated with resilience to the parasite. A similar approach has been recently reported in flat oyster O. edulis, where a major QTL related to resilience to Bonamia ostreae was identified (Vera et al, 2019;Sambade et al, 2022). Other selection models, such as overdominance, that have been reported for specific immune genes (Penn, 2002;Kekäläinen et al, 2009), could be operating and therefore our results would only explain part of the increased resilience.…”
Section: Discussionsupporting
confidence: 65%
“…Other selection models, such as overdominance, that have been reported for specific immune genes (Penn, 2002;Kekäläinen et al, 2009), could be operating and therefore our results would only explain part of the increased resilience. Furthermore, epigenetic imprinting is increasingly being claimed to be involved in immune memory in molluscs (Pradeu and Du Pasquier, 2018;Yao et al, 2021) and have also been suggested for bonamiosis resilience in flat oyster (Sambade et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These genomes provide researchers with new tools that empower genetic approaches addressing the ubiquitous threat posed by Bonamia via a range of technologies (Houston et al, 2020;Potts et al, 2021). In this regard, the genome reported here is proving useful already, with a recent study revealing that SNP markers previously associated with Bonamia resistance (Vera et al, 2019) are located in high linkage-disequilibrium across a large region of superscaffold 8, which contains many candidate immune genes (Sambade et al, 2022). Another recent study has mapped variants genotyped with an existing medium density SNP array (Gutierrez et al, 2017) against our new O. edulis genome, identifying QTLs underpinning variation in growth traits on super-scaffold 4 (Peñaloza et al, 2022).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, genetic markers which may indicate resistance or tolerance to B. ostreae have been identified (Sambade et al 2022), and many restoration efforts are now seeking to work with resistant or tolerant individuals in their active restoration efforts (Kamermans et al 2023). The effectiveness of the markers in response to a B. ostreae challenge have yet to be tested, but there is evidence that populations with a longer exposure history to B. ostreae or slow-growth life histories have better survival in the presence of the parasite (Culloty et al 2008;Egerton et al 2020).…”
Section: Invasive Species (Crassostrea Gigas)mentioning
confidence: 99%